Emotional intelligence and language learning performance of EFL learners in China: chain mediating effects of willingness to communicate and foreign language learning boredom - Wang, Ruoting; Xu, Qingshu (Frontiers in Psychology, 2026)
IntroductionEmotional intelligence (EI) has been widely recognized as a key affective factor in second language (L2) learning, yet its underlying mechanisms remain insufficiently explained. Drawing on Control–Value Theory (CVT), this study conceptualizes EI as a distal resource that enhances control–value appraisals, thereby fostering communicative engagement and mitigating negative achievement emotions, which jointly influence performance.MethodsA total of 1,158 Chinese undergraduates from seven universities completed validated measures of EI, willingness to communicate (WTC), foreign language learning boredom (FLLB), and submitted EFL test results. Structural equation modeling (SEM) was conducted using parcel-level indicators, and indirect effects were examined via bootstrap estimation (B = 5,000, BCa).ResultsThe hypothesized model demonstrated excellent fit and revealed that EI directly predicted language performance and indirectly influenced outcomes through both WTC and FLLB. Specifically, EI enhanced WTC, which reduced FLLB, and these factors jointly contributed to improved performance. Although the sequential (EI → WTC → FLLB → Performance) path was modest, it supported the theorized chain mediation mechanism consistent with CVT.DiscussionThe findings provide conceptual evidence that EI promotes language learning success not only by increasing communicative willingness but also by buffering against boredom—a low-control, low-value emotion. This integrative perspective advances a process-oriented account of how affective and motivational systems interact in L2 learning. Practically, it suggests that classroom interventions combining emotional competence training, autonomy-supportive pedagogy, and value-enhancing communicative tasks may strengthen engagement while alleviating boredom.